European Society of Endodontology position statement: endodontic management of traumatized permanent teeth. (20th June 2021) - ; Krastl, G.; Weiger, R.; Filippi, A.; Van Waes, H.; Ebeleseder, K.; Ree, M.; Connert, T.; Widbiller, M.; Tjäderhane, L.; Dummer, P. M. H.; Galler, K.
Abstract: This position statement represents a consensus of an expert committee convened by the European Society of Endodontology (ESE) on the endodontic management of traumatized permanent teeth. A recent comprehensive review with detailed background information provides the basis for this position statement (Krastl et al. 2021, International Endodontic Journal, https://doi.org/10.1111/iej.13508 ). The statement is based on current scientiﬁc evidence as well as the expertise of the committee. Complementing the recently revised guidelines of the International Association of Dental Traumatology, this position statement aims to provide clinical guidance for the choice of the appropriate endodontic approach for traumatized permanent teeth. Given the dynamic nature of research in this area, this position statement will be updated at appropriate intervals.